2014
DOI: 10.1016/j.expneurol.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival, axonal growth-promotion, and myelination of Schwann cells grafted into contused spinal cord in adult rats

Abstract: Schwann cells (SCs) have been considered to be one of the most promising cell types for transplantation to treat spinal cord injury (SCI) due to their unique growth-promoting properties. Despite the extensive use as donor cells for transplantation in SCI models, the fate of SCs is controversial due in part to the lack of a reliable marker for tracing the grafted SCs. To precisely assess the fate and temporal profile of transplanted SCs, we isolated purified SCs from sciatic nerves of adult transgenic rats over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
(67 reference statements)
5
23
0
Order By: Relevance
“…6). In a recent report, we showed that SCs isolated from this transgenic GFP-expressing SD rat strain showed proliferative and considerable survival potential as assessed through 1 year post-transplantation in a contusive SCI lesion produced in SD rats (Wang and Xu, 2014). As SD rats are outbred rats, this recent study involved long-term administration of the immunosuppressant cyclosporin A to repress potential rejection of the SC graft by the rats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…6). In a recent report, we showed that SCs isolated from this transgenic GFP-expressing SD rat strain showed proliferative and considerable survival potential as assessed through 1 year post-transplantation in a contusive SCI lesion produced in SD rats (Wang and Xu, 2014). As SD rats are outbred rats, this recent study involved long-term administration of the immunosuppressant cyclosporin A to repress potential rejection of the SC graft by the rats.…”
Section: Discussionmentioning
confidence: 92%
“…Prior to surgery, animals were randomly assigned to five groups: 1) Sham (n = 6), 2) Saline-treated only (Veh, n = 6), 3) bpV(pic) treated (n = 6), 4) GFP-SCs (n = 7), 5) bpV(pic) + GFP-SCs (n = 9). The experimental groups were established based on findings reported in previous publications testing the effects of bpV and SCs alone (Walker et al, 2012; Wang and Xu, 2014). In these experiments, the injury only groups and the injury plus saline group showed no difference.…”
Section: Methodsmentioning
confidence: 99%
“…These stem cells include NSCs, embryonic stem cells, induced potential stem cells (iPSCs), mesenchymal stem cells, fibroblast-derived stem cells, and transdifferentiated stem cells, which have been demonstrated to enhance partial axonal regeneration and even axon's ability to connect and communicate with other neurons, resulting in restoration [58][59][60][61][62]. Among the grafts, the fetal tissue, peripheral nerves, OECs, and Schwann cells can make the lesion area more conducive to regeneration by producing growth factors, cell adhesion molecules, and extracellular matrix components or recruitment of neurotrophins and construction of biobridges to guide axonal extension across the hostile post-injury spinal cord environment for axonal regeneration [61,62].…”
Section: Therapeutic Strategies For Spinal Cord Injurymentioning
confidence: 99%
“…There are also studies showing that the usage of Schwann cells in central nervous system injuries enhanced the regeneration process, and this effect was suspected to be provided by the secreted neurotrophins from the Schwann cells. According to Wang and Xu (2014), injection of Schwann cells directly into the lesion site at the midthoracic level in adult rats promoted myelination of regenerating axons. The transplanted cells survived until week 24 and migrated along the central canal.…”
Section: Discussionmentioning
confidence: 99%